Investigations on Wear Behaviour of AISI 4140 Hot Strip Mill Roller Hardfaced with Martensitic Stainless Steel by Submerged Arc Welding Process - R.V. Patel; S.P. Wanare; V.D. Kalyankar (Tribology in Industry, 2021)
In the present investigation, a worn-out hot strip mill roller of AISI 4140 material has been reconditioned by the deposition of hardfacing. The roller belongs to Arcelormittal Nippon Steel India, which is used to transfer metallic strip. This roller is continuously subjected to wear due to the oxide scale on the slab surface. Its regular maintenance and repair cause significant production loss. Therefore, two hardfacings of martensitic stainless steels with different composition are deposited on the surface of AISI 4140 steel by submerged arc welding and comparative analysis is performed to achieve the superior wear resistance. Further, hardfaced samples are evaluated on the basis of abrasive wear test, hardness, microstructure and worn-out morphology. The results showed that the hardfacing with combination of large volume fraction of martensite and small volume fraction of residual austenite attained the highest value of hardness up to 380 HV whereas the reverse combination showed 332 HV hardness and the minimum mass loss is observed for sample with 380 HV hardness. At the end, the most suitable material for the hardfacing of AISI 4140 is suggested. The outcomes of this work would be beneficial to improve the service life of roller of hot strip mill.